Keadilan Gender Pekerja Pada Usaha Komoditi Kopi Arabika Gayo di Kabupaten Bener Meriah - Mursyidin, Mursyidin; Darmansyah, Dedy; Yulianda, Riki; Fauzi, Fauzi; Hamsa, Amrizal (Jurnal Community, 2023)
Gender equality represents gender justice in various household activities, both in domestic and public spheres. The current issues are highly crucial and require special attention to enhance gender justice, as a means to improve women’s well-being. Gender justice is also observed in the realm of the coffe commodity busness concerning the employment of women in these units. The objective of this research is to analyze gender justice among workers in coffee commodity businesses in Bener Meriah District. The theoretical framework employed in this study is feminist theory, as it provides the analytical tools to examine gender discrimination using various sub-theoritical approaches. The reserch methodology is qualitative with a constructivist paradigm. Qualitative data analysis involves a descriptive analysis of earch gender issue prevalent in society. The results of this reserch addres four noteworthy gender issue: (1) Women’s roles in the public sphere concerning the coffee commodity business are still limited; (2) Many women workers continue to engage in voluntary, unpaid labor, as it has become a tradition for women to work in their own gardens and assist their husbands: (3) Women still uphold local wisdom and values prevalent in the community, such as engaging in rotational collective work during the coffee harvest; (4) Male dominance is observed in coffee shop employment, which may indicate an unequal absorption of female labor compared to male labor, or it might be attributed to a tradition rooted in the local community’s values and wisdom.